Revolutionizing Customer Service: Adaptive Workflow Automation for Case Management - Kesavareddi, Nishanth Kumar Reddy (International Journal of Computing and Engineering, 2025)
This comprehensive technical article examines the transformative potential of adaptive workflow automation in modernizing case management systems for customer service operations. The framework integrates Microsoft Power Platform capabilities with artificial intelligence to address persistent challenges, including lengthy resolution times, inconsistent protocol application, and fragmented multichannel experiences. By implementing intelligent routing algorithms, automated escalation protocols, predictive analytics, and omnichannel integration, organizations can significantly enhance operational efficiency while simultaneously improving customer satisfaction. The solution analyzes multiple dimensions, including ticket severity, SLA parameters, agent workloads, and historical performance to optimize case assignments and proactively identify at-risk cases before service failures occur. The article explores implementation benefits spanning resolution efficiency, compliance adherence, and employee satisfaction while addressing critical architectural considerations for successful deployment. Through phased implementation approaches that progressively expand capabilities, organizations can establish adaptable service infrastructures capable of evolving with changing customer expectations and technological capabilities.